Beneficial Effect of Arabica Coffee Fruit Skin (Coffea Arabica) on Epithelial Thickness after Tooth Extraction - Fadhila Zidni Ilma; Tecky Indriana; Agus Sumono (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2021)
Background: In Indonesia, tooth extraction is the most common practice in dentistry. A successful indicator of tooth extraction is a perfect healing process. One of the parameters of a perfect healing process is epithelial formation. Based on previous research, arabica coffee fruit skin has proven potential to accelerate the wound healing process. The compounds in the arabica coffee fruit skin are mostly composed of flavonoids, tannins, and chlorogenic acid. Purpose: This research is proposed to understand the beneficial effect of arabica coffee fruit skin (Coffea arabica) towards the increase of epithelial thickness in post tooth extraction socket. Material and Method: The type of this research was laboratory experimental in vivo with post-test only control group design using 24 Wistar rats as a sample. The sample was separated into two groups, control and intervention groups with 12 Wistar rats each. Treatment in both groups was given during 3, 5, and 7 days. Afterward, tissue processing undergoes with buccolingual cutting and HE coloring. Measurements are carried out with the ImageRaster software in the thickest and thinnest part of the epithelium that covers the tooth socket. Result: Epithelial thickness after tooth extraction increased significantly (p<0.05) in the intervention group compared to the control group. Conclusion: Arabica coffee fruit skin has the beneficial effect of increasing the epithelial thickness after tooth extraction.